(untitled) (Journal of the College of Basic Education, 2026)
Islamic movements began to appear in the Arab world in the last century, and in Egypt they regained their activity after the setback of 1967. The Islamic Group appeared in Upper Egypt, especially in Assiut Governorate. At first, it was an Islamic movement calling for the implementation of Islamic law. It was established within the halls of Egyptian universities, exploiting student unions to spread its ideas. Then, its work quickly shifted to the social and political side. It began to interfere in Egypt’s political affairs and even used violence to launch an Islamic revolution by assassinating Sadat